Reflection on Kitchens: The Culture of Restaurant Work by Gary Alan Fine - Clifford, Elizabeth (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This paper is based on the Fine book - Reflection on Kitchens: The Culture of Restaurant Work by Gary Alan Fine